A facile approach for the synthesis of nido-carborane fused oxazoles via one pot deboronation/cyclization of 9-amide-o-carboranes. Issue 6 (21st December 2018) - Zhang, Cai-Yan; Cao, Ke; Xu, Tao-Tao; Wu, Ji; Jiang, Linhai; Yang, Junxiao
Abstract : One pot deboronation/cyclization of 9-amide- o -carboranes for construction of nido -7, 8-carborane fused oxazoles. Abstract : A one pot deboronation/cyclization of 9-amide- o -carboranes for the synthesis of nido -7, 8-carborane fused oxazole by cooperation of Pd(OAc)2, AgOAc and K2 CO3 has been developed. A plausible mechanism involving an amide directed electrophilic palladation of the B–H bond and deboronation/cyclization process was proposed based on the successful isolation and structural characterization of the key deboronated intermediate.